Da classificação à promoção da aprendizagem: avaliação de alunos com altas habilidades/superdotação. - Moura, Lucimeire Alves (2009)
This research, in general, aimed to investigate the learning evaluation accomplished by teacher for students with academic giftedness in the areas of portuguese and mathematics. Specifically, intended to verify the type of strategy of learning evaluation used by the teacher for those students; to identify the criteria adopted in the elaboration of that evaluation and to analyze the student’s perfomance in those evaluations. The concept of giftedness has been developing from an unilateral notion to a multidimensional conception, based on the profile of capacities of the subject. Those students demand specific educational provisions in order to preservate and develop their abilities and to progress their learning, refering to the quality of teaching and evaluation methods. In that sense, it was proceeded an investigation of qualitative nature, in the form of a case study, with a sample composed by four teachers, whose students with academic giftedness in his/her regular classroom participated in the project Educar Igual a Motivar o Conhecimento Criativo (E=MC2), in Fortaleza-Ceará-Brazil, for gifted students. The following research instruments were used: non-participant observation, semi-structured interview and the learning evaluations of portuguese and mathematics. The data analysis revealed a significant divergence between theory and practice. This way, the learning evaluation, as it was accomplished, assumed a predominantly classificatory function, denying the necessary dynamic relationships to the construction of knowledge. The criteria adopted in their elaboration were based over all on the memorization and reproduction of knowledge, without the necessary assistance to the Special Education Needs of those students, that need to express and develop the creative thought. The students’ performance was on this side of their real capacities in reason of the prevalence of traditional pedagogic practices, that obstruct creativity and it is inadequate to the Special Education Needs of those students.